2017
DOI: 10.1186/s12960-017-0206-3
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals’ job satisfaction and associated factors at public health centers in West Ethiopia

Abstract: BackgroundHuman resources are vital for delivering health services, and health systems cannot function effectively without sufficient numbers of skilled, motivated, and well-supported health workers. Job satisfaction of health workers is important for motivation and efficiency, as higher job satisfaction improves both employee performance and patient satisfaction. Even though several studies have addressed job satisfaction among healthcare professionals in different part of the world, there are relatively few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
74
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 15 publications
12
74
4
1
Order By: Relevance
“…Health workers perceived training opportunity as scarce and not equitable in our study which was similar to the nding from a previous study done in Nepal in 2012 [27]. Inadequate career development opportunities affects the job satisfaction and ultimately the performance of health workers and health system as a whole which are supported by previous studies done in Nepal [28], India [29], Pakistan [30] and Ethiopia [24] . We thus suggest the need of in-service interventions such as further education and training opportunities for health workers working in primary health facility settings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Health workers perceived training opportunity as scarce and not equitable in our study which was similar to the nding from a previous study done in Nepal in 2012 [27]. Inadequate career development opportunities affects the job satisfaction and ultimately the performance of health workers and health system as a whole which are supported by previous studies done in Nepal [28], India [29], Pakistan [30] and Ethiopia [24] . We thus suggest the need of in-service interventions such as further education and training opportunities for health workers working in primary health facility settings.…”
Section: Discussionsupporting
confidence: 88%
“…This shows that health workers perceived that the existing salary and incentives were inadequate. Financial factor has been reported of associated with job satisfaction in studies around the world including China [21], Kenya [23], Ethiopia [24] and South Africa [25]. As remuneration is linked with meeting personal and family needs, we suggest the government for salary adjustment of health workers to improve job satisfaction.…”
Section: Discussionmentioning
confidence: 80%
“…Study conducted in western part of Ethiopia among health professional working in public health center, factors like Compensation (bene ts), recognition by management, and opportunity for development were associated with job satisfaction. A unit increase in salary and incentives and recognition by management scores resulted in 0.459 and 0.156 unit increases in job satisfaction scores, respectively (13). In another study conducted in Western Amhara region, Ethiopia, factors like presence of health professionals' reference manual/ guide, alcohol drinking, workload, experience, educational status and profession types were found to be signi cant factors associated with health care professionals' job satisfaction level.…”
Section: Introductionmentioning
confidence: 95%
“…Many studies have been conducted in different parts of Ethiopia to assess Employees satisfaction. In study conducted in western parts of Ethiopia, the overall level of job satisfaction among employees was 41.46% (13). In another study conducted in Ethiopia at western Amhara region the overall job satisfaction of health professional working at Western Amhara region was 31.7% (14).…”
Section: Introductionmentioning
confidence: 98%
“…Various factors accelerated and resulted in the migration of health professionals. Salary and incentives, recognition by management, developmental opportunities, and patient appreciation were strong predictors of job satisfaction in west Ethiopia [12]. Another study conducted in Eastern Amhara Region identified the presence of health professionals' reference manual/guide, alcohol drinking, workload, experience, educational status, and profession types were identified as important predictors for job satisfaction [13].…”
Section: Introductionmentioning
confidence: 98%